The Effect of The Use of Social Media on The Level of Product Sales in The Pandemic Period on Unisla Entrepreneurs - Levia Inggrit Sayekti (Institute of Computer Science (IOCS), 2020)
The real impact of the Covid-19 Pandemic on entrepreneurs was very large, many of whom suffered losses, namely in terms of sales decreased and not a few entrepreneurs were out of business due to the Covid-19 pandemic. One solution to the impact of the Covid-19 pandemic is to take advantage of social media such as Facebook, Instagram and Twitter as a means of increasing online sales. This study aims to enable entrepreneurial students to use social media as a means to help increase sales. The results showed the independent variables X1 (Instagram), X2 (Whatsapp), X3 (Facebook) and X4 (Twitter) had an effect on sales during the Covid-19 Pandemic, where researchers proved a significant effect simultaneously which can be explained by the f-test where f -count has a value of 36.608 at the real level of 5%, and a significance value of 0.000.